2020
DOI: 10.3390/jof6030136
|View full text |Cite
|
Sign up to set email alerts
|

Relative Frequency of Paradoxical Growth and Trailing Effect with Caspofungin, Micafungin, Anidulafungin, and the Novel Echinocandin Rezafungin against Candida Species

Abstract: Rezafungin is a next-generation echinocandin that has favorable pharmacokinetic properties. We compared the occurrence of paradoxical growth (PG) and trailing effect (TE) characteristics to echinocadins with rezafungin, caspofungin, micafungin and anidulafungin using 365 clinical Candida isolates belonging to 13 species. MICs were determined by BMD method according to CLSI (M27 Ed4). Disconnected growth (PG plus TE) was most frequent with caspofungin (49.6%), followed by anidulafungin (33.7%), micafungin (25.7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
10
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 26 publications
(60 reference statements)
0
10
0
Order By: Relevance
“…Another explanation for the weak fungistatic effect of echinocandins is that decreased amount of β-glucan induces a variety of stress adaptation pathways resulting in increased cell wall chitin [ 10 , 24 , 25 , 26 ]. Increased chitin content helps to stabilize the fungal cell wall, therefore mitigating the impact of echinocandins.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another explanation for the weak fungistatic effect of echinocandins is that decreased amount of β-glucan induces a variety of stress adaptation pathways resulting in increased cell wall chitin [ 10 , 24 , 25 , 26 ]. Increased chitin content helps to stabilize the fungal cell wall, therefore mitigating the impact of echinocandins.…”
Section: Discussionmentioning
confidence: 99%
“…Increased chitin content helps to stabilize the fungal cell wall, therefore mitigating the impact of echinocandins. Although this adaptive response does not lead to mutations in the FKS genes, the early adaptation to echinocandin exposure enhances survival of the drug effect and may allow the development of stable resistance mechanisms over time for surviving cells, possibly leading to clinical resistance in the long run [ 24 , 25 , 26 ]. The mini-paradoxical effect in RPMI-1640, which disappeared in the case of some isolates in the presence of serum, may represent such adaptation.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, it has been suggested that the aggregation may not be enough for C. auris isolates to overcome echinocandin exposure [ 10 ], while other mechanisms have also been proposed to explain the limited fungistatic activity of echinocandins, such as the increased cell wall chitin as a response to the decrease in the amount of β-glucan induced by the echinocandin exposure [ 27 , 28 ]. In this line, other reports found increased chitin amounts in C. auris , compared to other species more susceptible to echinocandin drugs [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Elevated chitin biosynthesis is linked with reduced susceptibility to echinocandins both in vitro and in vivo ( Perlin, 2015 ). Indeed, increased chitin content of cell wall has been observed during the paradoxical growth of Candida species, representing a rescue mechanism against high levels of echinocandins ( Stevens et al, 2004 ; Melo et al, 2007 ; Rueda et al, 2014 ; Toth et al, 2020 ). Additionally, ergosterol is a major constituent of the fungal plasma membrane ( Dupont et al, 2012 ).…”
Section: Discussionmentioning
confidence: 99%